2018
DOI: 10.1103/physrevb.98.024301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of phonons in Pd3Fe through the Curie temperature

Abstract: Iron phonon partial densities of states of Pd 3 57 Fe were measured from room temperature through the Curie transition at 500 K using nuclear resonant inelastic x-ray scattering. The experimental results were compared to ab initio spin-polarized calculations that model the finite-temperature thermodynamic properties of L1 2 -ordered Pd 3 Fe with stochastically generated atomic displacements, coupled with magnetic special quasirandom structures of noncollinear magnetic moments. The scattering measurements and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Early studies by Baltensperger and Helman 21 and Baltensperger 22 showed that the phonon frequencies of magnetic compounds depend on the spin order, and this type of interaction is still actively studied, mainly in the context of strongly correlated systems, in metallic oxides. Magnetism-dependent phonons were also found in relatively simple FM materials, such as body-centered cubic (bcc) Fe and Pd 3 Fe [23][24][25] . These FM materials exhibit phonon softening phenomena at elevated temperatures near T C , and several theoretical studies have revealed that this phonon softening is due to magnetic disordering [25][26][27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Early studies by Baltensperger and Helman 21 and Baltensperger 22 showed that the phonon frequencies of magnetic compounds depend on the spin order, and this type of interaction is still actively studied, mainly in the context of strongly correlated systems, in metallic oxides. Magnetism-dependent phonons were also found in relatively simple FM materials, such as body-centered cubic (bcc) Fe and Pd 3 Fe [23][24][25] . These FM materials exhibit phonon softening phenomena at elevated temperatures near T C , and several theoretical studies have revealed that this phonon softening is due to magnetic disordering [25][26][27][28][29][30][31][32] .…”
Section: Introductionmentioning
confidence: 96%
“…Magnetism-dependent phonons were also found in relatively simple FM materials, such as body-centered cubic (bcc) Fe and Pd 3 Fe [23][24][25] . These FM materials exhibit phonon softening phenomena at elevated temperatures near T C , and several theoretical studies have revealed that this phonon softening is due to magnetic disordering [25][26][27][28][29][30][31][32] . Regarding the predictive accuracy for T C , magnetism-dependent phonons, including the phonon softening, do not apparently seem to be related to T C .…”
Section: Introductionmentioning
confidence: 96%
“…These stochastically generated thermal displacements from Eqs. (2) and (3) sample the Born-Oppenheimer surface in the stochastically initialized temperature-dependent effective potential (s-TDEP) method [18][19][20]25,26]. This method approximates the inclusion of zero-point motion not included in AIMD simulations and connects seamlessly to the classical limit at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This method approximates the inclusion of zero-point motion not included in AIMD simulations and connects seamlessly to the classical limit at high temperature. The s-TDEP procedure can be used to calculate force constants capturing anomalous high-temperature effects [25][26][27][28] to low-temperature quantum effects [29,30] at a much lower computational cost than what is required by AIMD. The force constants calculated with this method are numerically converged with respect to the number of configurations and supercell size.…”
Section: Introductionmentioning
confidence: 99%
“…The other interaction is the effect of magnetic disordering on phonon frequencies. Some ferromagnetic materials such as bcc Fe and Pd 3 Fe shows phonon softening at elevated temperatures near T C [21][22][23] . Some research groups approached this phenomenon by different theoretical methods [23][24][25][26][27][28][29][30] and achieved the same conclusion: The phonon softening is due to magnetic disordering near T C .…”
mentioning
confidence: 99%